European Cinema Face to Face with Hollywood - Elsaesser, Thomas (Film Culture in Transition, 2005)
In the face of renewed competition from Hollywood since the early 1980s and the challenges posed to Europe's national cinemas by the fall of the Wall in 1989, independent filmmaking in Europe has begun to re-invent itself. European Cinema: Face to Face with Hollywood re-assesses the different debates and presents a broader framework for understanding the forces at work since the 1960s. These include the interface of "world cinema" and the rise of Asian cinemas, the importance of the international film festival circuit, the role of television, as well as the changing aesthetics of auteur cinema. New audiences have different allegiances, and new technologies enable networks to reshape identities, but European cinema still has an important function in setting critical and creative agendas, even as its economic and institutional bases are in transition.